Technology-enriched learning and retention of abstract concepts among first year electrical/electronic technology students in Nigerian Universities - Efuwape, Bamidele Michael; Efuwape, Oluwabunmi Asake (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2023)
Technology-enriched learning was integrated into the teaching of abstract concepts in electrical/electronic technology with investigation of its effects on students’ academic performance and learning retention. A quasi-experimental design was adopted for the study. All 178 technical education students specializing in electrical/electronic technology from the 4 universities offering the programme in the south-west, Nigeria were involved in the study. The achievement test instrument used for data collection has a reliability coefficient of .92 obtained through test retest technique. Six research hypotheses were tested in the study. Data collected were analysed using analysis of covariance (ANCOVA) at 0.05 level of significance. The findings of the study established that technology enriched learning significantly improves students’ academic performance (F(1, 169) = 12.707; p = .000) and retention (F(1, 169) = 94.097; p = .000) compared to traditional lecture method. It was recommended that the idea of technology-enriched learning should be adopted by university teachers to foster effective teaching of abstract concepts in science and engineering while traditional lecture method should be discouraged in the teaching of abstract concepts.